A comprehensive solution approach to the sustainability problem of photovoltaic systems: The Bolivian case. Issue 1 (1st January 2019) - Dávalos, Arturo; de Jesús Gil Herrera, Richard
Abstract: Assess the sustainability of electricity provision for rural families through off-grid Photovoltaic Systems (PVS) in Bolivia during the last 10 years, is the essential core of this research. The sustainability analysis is considered under a multidimensional approach: documental analysis complemented by a field research and semi-structured interviews with local experts. In the Bolivian case more than 36 thousand PVS have been installed in the last 10 years under different schemes, but more than 90% of these, are out of operation, shown the absence of sustainability approach in these interventions. For this and considering the international experience, is sketched a proposal under an integrality approach. The proposal contemplates substantial modifications in the way of granting the SFV to the families, their faculties as well as the institutional roles; a tariffed service has been suggested as it happens throughout an off-network system.